2014
DOI: 10.1371/journal.pone.0112807
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Physiological Responses of Cotton (Gossypium hirsutum L.) Plants to Salinity

Abstract: Salinization usually plays a primary role in soil degradation, which consequently reduces agricultural productivity. In this study, the effects of salinity on growth parameters, ion, chlorophyll, and proline content, photosynthesis, antioxidant enzyme activities, and lipid peroxidation of two cotton cultivars, [CCRI-79 (salt tolerant) and Simian 3 (salt sensitive)], were evaluated. Salinity was investigated at 0 mM, 80 mM, 160 mM, and 240 mM NaCl for 7 days. Salinity induced morphological and physiological cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
134
1
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(155 citation statements)
references
References 84 publications
17
134
1
3
Order By: Relevance
“…5a). In response to oxidative stress, antioxidant system is often stimulated to provide essential protection for plants, and then antioxidant capacity can be used to discriminate salt tolerance among crop varieties (Ashrafi et al 2015;Kiani-Pouya 2015;Neto et al 2006;Sairam et al 2005;Zhang et al 2014). Accordingly, it was reported that salt priming improved antioxidant protection and helped to Fig.…”
Section: Discussionmentioning
confidence: 99%
“…5a). In response to oxidative stress, antioxidant system is often stimulated to provide essential protection for plants, and then antioxidant capacity can be used to discriminate salt tolerance among crop varieties (Ashrafi et al 2015;Kiani-Pouya 2015;Neto et al 2006;Sairam et al 2005;Zhang et al 2014). Accordingly, it was reported that salt priming improved antioxidant protection and helped to Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, rates of transpiration (i.e., water loss) and photosynthesis (CO 2 uptake) are also reduced. Indeed, in cotton plants submitted to salt stress treatments, a substantial reduction in photosynthesis has been associated with a decrease in total chlorophyll content and distortion in chlorophyll ultrastructures (Zhang L. et al, 2014). It has been also evoked that sink to source feedback inhibition would moderate the rate of photosynthesis to match the reduced demand arising from growth inhibition (Paul and Foyer, 2001).…”
Section: Impact Of Soil Salinization On Plant Growth and Survivalmentioning
confidence: 99%
“…Thus, they work together to Abbreviations: APX, ascorbate peroxidase; AsA, ascorbate; CAT, catalase; ETR, electron transport rate; Fv/Fm, the maximal photochemical capacity of PSII; H 2 O 2 , hydrogen peroxide; MDA, malondialdehyde; NADPH, nicotinamide adenine dinucleotide phosphate; O 2 , superoxide anion; PAL, phenylalanine ammonia-lyase; Pn, Photosynthetic rate; PSI, photosystem I; PSII, photosystem II; ROS, reactive oxygen species; SOD, superoxide dismutase; DMR/MR 0 , the maximal photochemical capacity of PSI.limit the generation of hydroxyl radical by controlling the levels of O 2 À and H 2 O 2 . Under saline stress, plant antioxidant system is often stimulated to defense oxidative injury, and antioxidant capacity has been used as a criterion for the comparison of salt tolerance among crop cultivars (Ashrafi et al, 2015;Kiani-Pouya, 2015;Zhang et al, 2014). Phenolic compounds which are secondary metabolites have high ROS scavenging capacity, and accumulation of phenolics is commonly considered as a positive self-protection way to strengthen ROS scavenging ability in plants upon salt-induced oxidative stress (Abrol et al, 2012;Colla et al, 2013;Falleh et al, 2012;Ksouri et al, 2007;Shao et al, 2015;Zhao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%